Analysis of Code Mixing in the Lyrics of the Song 'Boys Meet You' - Netya Pradnyamita, Komang (Educationist: Journal of Educational and Cultural Studies, 2023)
This study aims to analyze the code mixing in the lyrics of the song "Boys Meet You" specifically to describe the types of code mixing contained in the song lyrics and also to describe the factors that influence the occurrence of code mixing in the song lyrics. The method used in this research is descriptive qualitative method. The type of code mixing contained in the lyrics of the song "Boys Meet You" is outer code-mixing, for example, the constituent baby cute of the sentence "mabushi sugiru yo baby cute" (眩しすぎるよ baby cute) which uses English in these lyrics can be said to be external code-mixing, while the factors that cause code-mixing in the lyrics of the song "Boys Meet You" are factors of relaxedness or informal situations, language inappropriate factors and educated factors of the speech actors.